2015
DOI: 10.1682/jrrd.2014.09.0209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prosthetic limb prescription on 3-year mortality among Veterans with lower-limb amputation

Abstract: Our objective was to determine the relationship between receipt of a prescription for a prosthetic limb and three-year mortality post-surgery among veterans with lower extremity amputation. We conducted a retrospective observational study that included 4,578 veterans hospitalized for lower extremity amputation and discharged in Fiscal Years 2003 and 2004. The outcome was time to all-cause mortality from the amputation surgical date up to the 3-year anniversary of the surgical date. There were 1,300 (28.4%) vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…It has implications on quality of life 11,23 and may impact mortality. 24 We found that obtaining and successfully using a prosthetic leg was closely tied to the perception of a successful functional recovery by participants. However, despite all patients having participated in rehabilitation postoperatively, many felt that this was insufficient.…”
Section: Discussionmentioning
confidence: 84%
“…It has implications on quality of life 11,23 and may impact mortality. 24 We found that obtaining and successfully using a prosthetic leg was closely tied to the perception of a successful functional recovery by participants. However, despite all patients having participated in rehabilitation postoperatively, many felt that this was insufficient.…”
Section: Discussionmentioning
confidence: 84%
“…The primary finding of financial benefits coinciding with earlier delivery of a prosthesis is in alignment with previous evidence regarding the clinical benefits of early fitting of a prosthesis. 17 , 21 , 23 Proposed clinical practice guidelines have suggested that intervention with a prosthesis early in the rehabilitation process is critical to individual physical health and improved quality care and promotes cost-effective patient management. 24 There is a likelihood of different healing rates among patients post-LLA.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data would suggest that if a patient does not receive a custom prosthesis within 12 to 18 mos, it is possible for the individual to decline to a health state so poor that they are considered unlikely to benefit from a prosthesis. 8 , 17 About 30% to 60% of adults exclusively use a wheelchair after LLA, which significantly reduces quality of life, independence, and cardiovascular health. 18 However, adults who receive early rehabilitation after a transtibial amputation have improved mobility compared with matched individuals with no rehabilitation services and up to 80% lower hazard of death if they are a prosthesis user.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kurichi et al . 2015; Littman et al . 2014), our focus in this systematic review is on the first group whose injuries are ‘service attributable’.…”
Section: Introductionmentioning
confidence: 99%